Tetraaquabis(2,3-dihydro-1,4-benzodioxine-2-carboxylato)calcium(II) - Camargo Cortés, Esmit B. (2020)
The acid–base reaction of 1,4-benzodioxane 2-carboxylic acid with calcium carbonate furnished the centrosymmetric title compound, [Ca(C9H7O4)2(H2O)4], in which the metal ion is octahedrally coordinated by two monodentate 1,4-benzodioxane 2-carboxylate ligands and four water molecules. In the crystal, O—H...O and C—H...O hydrogen bonds link the molecules into a three-dimensional network.